2022
DOI: 10.34190/ejel.20.1.2190
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Romanian Engineering Students’ Perceptions of Covid-19 Emergency e-Learning Situation. A Mixed-Method Case Study

Abstract: The Covid-19  pandemic is the most disturbing event in the lifetime of most of our planet’s citizens. The lockdown measures directly impacted many areas of our lives, including the educational sector, because locking down countries meant implicitly locking down the educational system. Moreover, what was first considered a temporary solution for an extraordinary situation began to look more and more like a medium to long-term general rule. Nevertheless, the questions are: are we all ready to move the entire edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
(69 reference statements)
2
7
0
Order By: Relevance
“…Particularly with regard to students in higher education, research reports that the pandemic had an impact on several dimensions of students' lives, including their lifestyle, interpersonal competences, behaviors, emotions, feelings, and educational experiences [19,[30][31][32]. Studies from different parts of the globe indicate some common issues experienced by students, such as a decrease in motivation due to social aspects and especially a lack of communication and interactions with teachers and peers [33][34][35][36]. In a systematic literature review carried out at the beginning of the pandemic crisis in 2020 on The Impact of Social Isolation and Loneliness on the Mental Health of Children and Adolescents in the Context of COVID-19, the authors found 83 articles that addressed this topic [37].…”
Section: Impact Of Covid-19 On Studentsmentioning
confidence: 99%
“…Particularly with regard to students in higher education, research reports that the pandemic had an impact on several dimensions of students' lives, including their lifestyle, interpersonal competences, behaviors, emotions, feelings, and educational experiences [19,[30][31][32]. Studies from different parts of the globe indicate some common issues experienced by students, such as a decrease in motivation due to social aspects and especially a lack of communication and interactions with teachers and peers [33][34][35][36]. In a systematic literature review carried out at the beginning of the pandemic crisis in 2020 on The Impact of Social Isolation and Loneliness on the Mental Health of Children and Adolescents in the Context of COVID-19, the authors found 83 articles that addressed this topic [37].…”
Section: Impact Of Covid-19 On Studentsmentioning
confidence: 99%
“…The results show that the new method of the proposed form can provide close scores compared to the paper-based model by a deviation of 0.6%. Another recent study by Alexa et al ( 2022 ) investigates the relationship between using the E-learning features and engineering students. The research surveys 134 engineering students and reveals that regardless the engineering students know much better the technologies than other filed, the students are still facing difficulties in accommodating E-learning advantages and including them in their study routine.…”
Section: Literature Review Of Relevant Studiesmentioning
confidence: 99%
“…Arif ( 2021 ) described the use of virtual reality in teaching in engineering, in which a connection assessment unit was planned for a cave automatic virtual environment-based system, called “Projection VR” and installed at the NED University Virtual Reality Center. Alexa et al (2022 ) assessed the spread of changes, access, and integration of new technologies in online learning during the coronavirus-2019 pandemic in 134 engineering students at the Technical University of Lasi. In their study, 80.6% of students reported having resources to study in virtual classrooms and the ability to work in virtual platforms.…”
Section: Related Workmentioning
confidence: 99%